Effects of high-intensity interval training in a cold environment on arterial stiffness and cerebral hemodynamics in sedentary Chinese college female students post-COVID-19 - Chen, Xiangyuan; Hu, Niyuan; Han, Huifeng; Cai, Guoliang; Qin, Ying (Frontiers in Neurology, 2024)
Many patients with COVID-19 experience increased arterial stiffness and abnormal cerebral hemodynamics. Although previous studies have explored the effects of cold environments on cardiovascular health and cerebral hemodynamics, there is still no research on the changes in cardiovascular and cerebral hemodynamics in sedentary female students recovering from COVID-19 while performing high-intensity interval training (HIIT) in cold environments. This study investigates the effects of 1 week of HIIT in a cold environment on cerebral hemodynamics and arterial stiffness (AS) in sedentary female college students, providing new insights into the pathophysiological mechanisms in this specific context. Thirty-six participants were randomly divided into a control group (n = 12), a room temperature (RE) group (n = 12), and a cold environment (CE) group (n = 12). HIIT was performed for four 4-min running training sessions, with a 4-min interval between each training session, The training duration was 1 week, with a frequency of 2 sessions per day, while the control group did not undergo any training. After training, the AS in the CE group significantly decreased (p < 0.05), with an average reduction of 11% in brachial-ankle pulse wave velocity, showing a significantly greater improvement compared to the RE group and the control group (p < 0.05), while no significant changes were observed in the RE group (p > 0.05). In the Y-Balance Tests (YBTs), the concentrations of cerebral oxygenated hemoglobin and total hemoglobin significantly increased (p < 0.05) during unilateral leg support tests in both the CE and RE groups, and the increase of CE group is greater than that of RE group. In contrast, in the control group, the concentrations of cerebral oxygenated hemoglobin and total hemoglobin significantly decreased during left leg support (p < 0.05). Our study found that performing HIIT in a cold environment not only effectively reduces AS in sedentary female college students after COVID-19, improves cardiovascular function, but also significantly enhances cerebral hemodynamics, helping them alleviate the negative impacts of post-COVID-19 sequelae and sedentary behavior on health. Future research should further explore the mechanisms by which sedentary behavior, post-COVID-19 recovery status, and adaptation to cold environments collectively influence cardiovascular function and cerebral hemodynamics, providing a more comprehensive understanding of these factors.